Chapter Percorsi familiari e preminenza a Nola alla fine del Medioevo. Il caso degli Albertini di Cimitile - Tufano, Luigi (Reti Medievali E-Book, 2021)
Through the parchments of the aristocratic archive, the essay reconstructs the events and paths of construction and consolidation of the political and social role of the Albertini of Cimitile, an important family of the Nolan élite, of legal professionals and with consolidated relations with the Orsini count dynasty, in the period between the late Middle Ages and the early modern period.